PENGEMBANGAN SUMBER DAYA MANUSIA STRATEGIS DI SEKOLAH ISLAM: MENILAI DAMPAK PELATIHAN, KOMPETENSI, DAN DUKUNGAN ORGANISASI TERHADAP KINERJA GURU - Faiz Akmal Baihaqi; Siti Aimah (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze the effectiveness of Strategic Human Resource Development (SHRD) in improving madrasah teacher performance through three main components: training quality, Islamic value-based teacher competencies, and organizational support. The research method employed a quantitative approach with an explanatory survey of 151 MTs (Islamic Junior High School) and MA (Islamic Junior High School) teachers. The instrument used was a Likert-type questionnaire, tested for construct validity and reliability using Cronbach's Alpha. Regression analysis was used to examine the partial and simultaneous effects between variables. The results showed that training significantly improved planning skills and material mastery, while teacher competency was the most dominant variable through pedagogical, professional, and Islamic spiritual aspects. Organizational support was also significant through supervision, facilities, and a collaborative culture. Theoretically, this study enriches the literature on Islamic value-based HRD and practically provides strategic recommendations for developing madrasah human resources in the digital era.